HUBUNGAN ANTARA KEHILANGAN GIGI DAN KESEHATAN GIGI DENGAN KUALITAS HIDUP LANSIA DI PUSKESMAS LUBUK BUAYA KECAMATAN KOTO TANGAH - Rahmat Dwi Putra Perkasa; Eni Rahmi; Ilmiawati Ilmiawati (Andalas Dental Journal, 2018)
Tooth loss is a problem of dental and oral health that is often found in every individual. The prevalence of tooth loss increases with increasing age in a person, especially in the elderly. Tooth loss causes a decrease in oral function, especially in the function of mastication and physical function in the elderly, which then affects the quality of life. To determine the relationship of tooth loss with quality of life related to oral health in the elderly at Puskesmas Lubuk Buaya Kecamatan Koto Tangah.. The research uses observational analytic with a cross sectional study approach to 105 elderly people (≥ 60 years). Data collection was carried out by means of general interviews with respondents followed by oral examinations and lastly an interview was conducted using the Oral Health Impact Profile-14 questionnaire (OHIP-14). Data analysis used in this study is Chi-square statistical test. The elderly population in Kecamatan Koto Tangah had an average of 5-10 tooth loss with the most distribution were posterior tooth loss. As many as 50.5% of elderly people in Kecamatan Koto Tangah had a good quality of life. The majority of respondents with anterior-posterior tooth loss showed poor quality of life. Chi-square test showed that there was a significant relationship between the number of tooth loss and quality of life related to oral health (p <0.001; OR=16.127) and there was a significant relationship between the location of tooth loss and quality of life related to oral health (p <0.001 ; OR=9,274).